Remote and Flexible work: A Systematic Review - Parajuli, Suman Kamal (Nepal Journal of Multidisciplinary Research, 2023)
The primary objective of this study was to discover the present state of Remote and Flexible work research. In order to facilitate the systematic review process, this investigation follows a predetermined procedure. The dataset for this research consisted of 101 publications published over a period of 13 years. This study explores four themes; the study related to identifying the relationship between employment engagement and flexible work arrangements, the concept and the literature were also concerns. Researchers also attempted to address solution to remote and flexible work issues and explore their challenges. Flexible work arrangements might be investigated to solve security issues, organizational sectors and humanity as a whole might benefit from such a study.